Strengthening the Role of Village-Owned Enterprises for Agriculture and Livestock SMEs - Prasetya Nugeraha; Maulana Agung Pratama; Diang Adistya; Ahmad Efendi; Winda Septiani; Firman Handika; Siska Febryani; Rachmawati Lola Widisono; Murni Sari; Cristofer Ami Nugroho; Suprihatin Ali (Iapa Proceedings Conference, 2022)
Village-Owned Enterprises, or BUMDes, are local business institutions that use village resources to enhance the village economy. However, in numerous locations where BUMDes already exist, some of these BUMDes are not working smoothly and are inactive. As a result, the construction of a BUMDes business unit must be tailored to the capabilities of the community. The purpose of this research is to explore more into the role of BUMDes for SMEs in agriculture and livestock. This study employed a qualitative research method with a descriptive approach. This study's data is derived from primary sources. While data gathering is accomplished by the use of observation, interviews, and documentation. According to the study's findings, BUMDes Purworejo and BUMDes Lugusari have been able to support the community's economy in their villages, where the majority of residents work in the agricultural and livestock industries. BUMDes Purworejo and BUMDes Lugusari contribute to the village economy through business units such as PAMDes, Quail Farms, Village Markets, and Pond Management Businesses.